On the diversity of subterranean beetles of the Dinarides: new leiodid taxa (Coleoptera: Leiodidae) from Serbia - Ćurčić, Srećko; Pavićević, Dragan; Vesović, Nikola; Vrbica, Maja; Kuraica, Miloš; Marković, Đorđe; Petković, Matija; Lazović, Vladimir; Pantelić, Dejan; Bosco, Fabrizio (European Journal of Taxonomy, 2021)
Three subterranean leptodirine leiodid taxa, viz., Bozidaria Ćurčić & Pavićević gen. nov., Bozidaria serbooccidentalis Ćurčić & Pavićević gen. et sp. nov. and Proleonhardella (Proleonhardella) tarensis Ćurčić & Pavićević sp. nov., are described and diagnosed. Bozidaria Ćurčić & Pavićević gen. nov. belongs to the phyletic series of “Leonhardella”. The new beetle taxa differ from their closest relatives in numerous morphological characters. They most likely belong to phyletic lineages of Pliocene age. The new leiodid taxa are endemic to the Dinaric mountain chain of western Serbia. Keys to the leptodirine leiodid genera of the phyletic series of “Leonhardella” and to the taxa of the genus Proleonhardella Jeannel, 1910 are included.